Implementasi Stategi Writing to Learn Pada Topik Fluida Dinamis Untuk Meningkatkan Keterampilan Berpikir Kritis dan Keterampilan Berkomunikasi Siswa SMA - Diah Ayu Ratna Wulan, - (2022)
The aim of this study was to indentify the effectiveness of the writing to learn strategies to improving critical thinking skills and communication skills of high school students. The research method used was a quantitative quasi-experimental design with the research design a nonequivalent control group design. The population in this study were all students of class XI MIPA in a senior high schools in Bandung. The sample of this study amounted to 63 students of class XI in a senior high schools in Bandung. The sampling technique in this study used was purposive sampling. The instrument used to measure critical thinking skills was the Watson-Glaser Critical Thinking Appraisal (WGCTA) test, which consisted of 55 questions, while to measure communication skills, a writing task was used in the form of a learning journal. The data analysis technique used to determine the improvement of thinking skills and communication skills is using the n-gain calculation, while to determine the effectiveness of the writing to learn strategy using the Mann Whitney U test and effect size. The results showed that the class that applied the writing to learn strategy had a higher critical thinking skill improvement than the class that did not apply the writing to learn strategy. In the experimental class, the n-gain value of critical thinking skills is <g>=0.531 which is in the medium category. While the control class only has a critical thinking skill n-gain value of <g>=0.107 which is in the low category. For the effect size calculation results, critical thinking skills have a value of 2.26 where these results are included in the high category. Meanwhile, the n-gain value in the experimental class communication skills has a value of 0.53 which is included in the medium category.